View Single Post
AKG
#7
Sep9-05, 04:15 PM
Sci Advisor
HW Helper
P: 2,586
-a(iq + x/a)/2 = -a(iq + ix/ia)/2 = -a(i(q - ix/a))/2 = -ai(q - ix/a)/2 = a(q - ix/a)/2, so your exponent is just the negative of mine. However, I'm pretty sure I completed the square correctly. Also, when you complete the square, say, in the variable q, then you want to end up with something of the form A(q - B) + C, you shouldn't have iq or anything like that (you should have factored the i out, but there was no i to factor). Actually, you should be able to see that yours is wrong, because when you square it, the q term will be -a(iq) = aq, but we know that the original thing we were working with had -aq as the q term.